Processo tributário e Inteligência Artificial - Souza Júnior, José Ildo de (2024)
This dissertation investigates the application of artificial intelligence in the tax process, its impact on the fundamental rights of taxpayers and the balance of the tax obligation relationship. The research analyzes the risks inherent to the use of this technology in tax deals, in the light of due process, especially in the performance of decision-making function. The results indicate that the increasing use of artificial intelligence tools has generated greater speed in the tax process when applied in bureaucratic activities, but the allocation of decision-making functions to robots is surrounded by risks, due to discriminatory biases, lack of transparency of algorithmic systems and difficulty in dealing with unprecedented situations, which can perpetuate injustices against taxpayers. It is concluded that, since technological innovation is something unstoppable, a minimally safe implementation of artificial intelligence in the tax process requires the observance of tax constitutional principles, which should allow transparency, predictability, oversight mechanisms of the decision-making process, non-discrimination and correction of biases, data protection, risk mitigation and remediation of possible damages